THE ESSENCE OF THE BANKING SECTOR DEBT SECURITY OF THE NATIONAL ECONOMY - Cоловаров Андрій (Socio-economic relations in the digital society, 2019)
The significance of the banking sector debt security is determined. In-depth theoretical understanding of debt resources, their place and role, as well as movement / circulation in the national economy. The author’s vision of the debt-debt cycle in the national economy is presented. Considered views on the ratio of debt and credit. The illegality of debt and credit opposition is proved. Characterized by the points of scientists on assigning debt security to economic / financial security. Analyzed the opinions of scholars on debt security of the state and banking sector debt security. Th e author’s defi nition of the essence of debt security of the banking sector of the national economy is presented. Th e banking sector debt security is considered as a certain level of credit and debt strategy / banking sector policy; debt situation of the banking sector; the size of the creditors’ remuneration; the level of debt load on the budget of clients of the banking sector; the state of state regulation of debt, corporate governance in the banking sector, securing the debt of the banking sector for loans and debt securities.